GESTIÓN DE EXPATRIADOS: UN RETO PARA LAS EMPRESAS NACIONALES - Tito Huamaní, Pedro Leonardo (2009)
This paper refers to treatment that companies give “in terms of human management” to its directors, officers or highly skilled professionals, who have for convenience in their subsidiaries abroad. The internationalization of the firm is a decision of significance, which essentially reflects the level of growth and development, is understood in the context of productivity and competitiveness not only nationally, but primarily at the international level. This decision implies decisions other side, as that of defining who or who will be responsible for managing the subsidiary or subsidiaries. When the firm moves from the export of internationalization, via subsidiary or joint venture, will be very interested with an official guarantee of their entire confidence, the success of its operations since its inception. This concern of successful management and security of your control, is what workers have to bet on national will manage the subsidiary or branch in other countries. This group of Directors/Officers are known as expatriates. So managed from the international perspective to such workers, it becomes a challenge for headquarters personnel or human resources of enterprises. In Latin America and particularly in Peru, the treatment that makes this group of workers is a novelty, given that very few of them are in this phase: Ajegroup, Grupo Gloria, Group Credit, being other. In this regard, the theory refers to the successful companies in global environments have placed considerable emphasis on its human talent, as one of the key success factors of their internationalization processes. The global mindset is taking hold in a company where all employees feel in the world as a natural market. This mental attitude definitely affects production processes, business and efficiency of operational processes. Thus, globalization introduces and requires a new attitude of its human talent, particularly in those who have responsibility for directing the foreign subsidiaries. The first part of this paper we review the broad theory related to the Management of Expatriates, analyzing the pros and cons of this decision in the context of the cultures of the countries of destination. Similarly, we try to demonstrate the importance for enterprises, management of its expatriate staff in destination countries, describing what is happening at Latin America, particularly Peru level. In the contrastive or empirical evidence discussed the successful experience of internationalization Ajegroup (Group Añaños), a company born in the bowels of a provincial city (Huamanga), which is now a reference in the internationalization process domestic firms. Finally, we believe that internationalization and within the management of expatriate workers, is a phenomenon that must undergo many domestic firms, in the context of the validity of the Treaties of Free Trade Agreements (FTAs) signed between our country and the United States America (USA), the European Community (EC), China, Chile, etc. This part will be important to continue analyzing the experiences of some neighboring countries, who have more experience than us, such as Mexico, Chile, Brazil, among others.